An Analysis of Teachers' Professional Teaching Competence at Sanggar Under the Guidance of Sekolah Indonesia Kuala Lumpur, Malaysia - Nurainiah; Abubakar Mekkah; Muhammad Syarif; Septhia Irnanda; Faisal Anwar; Wan Balqis Zulkarnain; Raina Feriska Rusyadi (Jurnal Sociohumaniora Kodepena (JSK), 2025)
Teacher professional competence is one of the key factors determining the quality of the teaching and learning process, particularly in educational institutions serving students with unique characteristics, such as Sanggar Bimbingan (SB) in Malaysia. Teachers at Sanggar Bimbingan Semenyih, Kuala Lumpur, are required not only to possess strong subject matter knowledge but also to adapt their instructional strategies to the diverse academic, social, and cultural backgrounds of their students. This study aims to analyze the professional competence of teachers in implementing the teaching and learning process at Sanggar Bimbingan Semenyih, Kuala Lumpur. The research employed a qualitative approach using a case study method. Data were collected through classroom observations, in-depth interviews, and document analysis involving the school principal, teachers, and instructional documents. The data were analyzed through the stages of data reduction, data display, and conclusion drawing, while source and technique triangulation were applied to enhance the credibility of the findings. The results indicate that the teachers demonstrated good professional competence through mastery of subject content, preparation of instructional plans, implementation of diverse teaching methods, and effective use of instructional media in accordance with the school's conditions. Nevertheless, several challenges remain, including limited learning facilities, the heterogeneous abilities of students, and insufficient opportunities for continuous professional development. This study concludes that strengthening continuous professional development programs, enhancing institutional support, and providing adequate learning facilities are essential to improving teachers' professional competence, thereby enabling a more effective and sustainable teaching and learning process at Sanggar Bimbingan Semenyih, Kuala Lumpur